Acetyl-protected cytosine and guanine containing acrylics as supramolecular adhesives. Issue 2 (28th January 2019) - Zhang, Keren; Fahs, Gregory B; Margaretta, Evan; Hudson, Amanda G; Moore, Robert B; Long, Timothy E.
ABSTRACT: Hydrogen bonding among nucleobase pairs serves as an efficient noncovalent interaction for designing supramolecular polymers with desired properties for pressure sensitive adhesives. Michael addition yielded acetyl-protected cytosine/guanine containing acrylic monomers with flexible spacers between the hydrogen bonding units and the acrylic backbone. Free radical polymerization of nucleobase-containing monomers afforded acetyl-protected cytosine/guanine homopolymers and random copolymers with n -butyl acrylate. Nucleobase incorporation significantly affected thermal, thermomechanical, rheological, morphological properties, and adhesive performance of polyacrylates. Guanine/cytosine-containing copolymers each exhibited a single glass transition (Tg ) that increased with increasing nucleobase content. Self-association of acetyl cytosine and acetyl guanine units converted low Tg polyacrylates to physically crosslinked networks with mechanical integrity. Solution casting acetyl guanine-containing copolymers with 8 mol% or higher guanine content yielded free-standing films with microphase-separated morphologies. Acetyl cytosine-containing copolymers with 15 mol% or more cytosine formed free-standing films with less microphase-separation compared to the guanine copolymers. 1 H NMR titration experiments established a 1:1 binding stoichiometry between acetyl cytosine and acetyl guanine monomers in CDCl3, similar to guanine-cytosine association. However, the acetyl protecting group hindered the formation of triple hydrogen bonding, resulting in double hydrogen bonding between acetyl cytosine and acetyl guanine with an intermediate binding strength comparable to their self-associations. Acetyl guanine-containing copolymers with 3 mol% acetyl guanine exhibited higher peel strength on stainless steel and higher extended service frequency range compared to cytosine-containing copolymers and various pressure sensitive adhesive controls.